ANALISIS KESULITAN SISWA SMP DALAM MEMAHAMI KONSEP KUBUS BALOK - Maryanih Maryanih; Euis Eti Rohaeti; M Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The descriptive research aims to diagnose the difficulties of secondary school students in understanding Cube and Rectangular Prism. Geometry test and interview are used as the instrument. The subjects are 3 seventh grade students who respectively represent high, medium and low ability in mathematics. This research finds that the students have difficulties in understanding the properties of a cube and rectangular prism, inventing the surface area, and using the formula to determine the surface area. The difficulty in using the formula to solve related problems is an effect of memorizing ready-made formula without understanding so the students are easy to forget it. The alternative ways to cope with the difficulties are: (a) Using computer application (PowerPoint, Ms. Word with SmartArt Graphic) and other current software like Cabri Geometry, The Geometer’s Sketchpad (GSP), Geometry Expert, Logo, Geogebra, and Wingeom; (b) Activating students’ prior knowledge about plane which explains the side of the solid figures; (c) Implementing guided discovery learning with students’ worksheet; and (d) giving variation exercises involving contextual or non-contextual problems.